Las entrevistas y el otro en la Historia reciente: el rol de las categorías nativas - Urteneche, Gonzalo (Historiografías, 2024)
Abstract This article examines the use of so-called native categories in the historiography on recent history, considering the influence of the viewpoint of actors through the process of production of historical knowledge. It explores the challenge involved in the balance between the critical distance of historian and the narratives of protagonists, using their testimonies as an evidence. The proposal is developed through a comparative analysis with anthropology and the examination of specific cases from Argentine historiography on recent history. By analyzing works such as Los combatientes by Vera Carnovale and Los montoneros del barrio by Javier Salcedo, the article explores how native categories might be integrated into the historiographical discourse. It concludes that the role assigned by the historian to perspectives of actors determines the potential for the collective construction of knowledge of recent history. Keywords Native categories, interview, testimony, Argentine historiography, recent history